Controlled drug release through regulated biodegradation of poly(lactic acid) using inorganic salts - Kumar S.; Singh S.; Senapati S.; Singh A.P.; Ray B.; Maiti P. (My University, 2025)
Biodegradation rate of poly(lactic acid) (PLA) has been regulated, both increase and decrease with respect to the biodegradation of pure PLA, by embedding meager amount of inorganic salts in polymer matrix. Biodegradation is performed in enzyme medium on suspension and film and the extent of biodegradation is measured through spectroscopic technique which is also verified by weight loss measurement. Media pH has been controlled using trace amount of inorganic salt which eventually control the biodegradation of PLA. High performance liquid chromatography confirms the hydrolytic degradation of PLA to its monomer/oligomer. Induced pH by metal salts show maximum degradation at alkaline range (with calcium salt) while inhibition is observed in acidic medium (with iron salt). The pH of media changes the conformation of enzyme which in turn regulate the rate of biodegradation. Thermal degradation and increment of modulus indicate improvement in thermo-mechanical properties of PLA in presence of inorganic salts. Functional stability of enzyme with metal salts corresponding to acidic and alkaline pH has been established through a model to explain the conformational changes of the active sites of enzyme at varying pH influencing the rate of hydrolysis leading to regulated biodegradation of PLA. The tuned biodegradation has been applied for the controlled release of drug from the polymer matrix (both sustained and enhanced cumulative release as compared to pure polymer). The cell proliferation and adhesion are influenced by the acidic and basic nature of polymeric material tuned by two different inorganic salts showing better adhesion and proliferation in calcium based composite and, therefore, suggest biological use of these composites in biomedical applications. © 2017 Elsevier B.V.